Molybdenum disulfide slurry for electrophoretic coating of fastener, preparation method of molybdenum disulfide slurry and electrophoretic coating method of fastener

By using a slurry composed of molybdenum disulfide, epoxy acrylic cathode electrophoretic resin and water, combined with electrophoretic coating technology, the problem of uneven coating of molybdenum disulfide on small-sized threaded fasteners is solved, and dense and uniform film layer formation and locking performance are improved.

CN119570341APending Publication Date: 2025-03-07XINYANG AEROSPACE FASTENER FACTORY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411791363.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to uniformly form a molybdenum disulfide coating on small-sized threaded fasteners, resulting in uneven coating thickness and poor locking performance.

Method used

A slurry consisting of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is used to strictly control the particle size of molybdenum disulfide and the conductivity of the slurry, combined with electrophoretic coating technology, a dense and uniform molybdenum disulfide film layer is formed.

Benefits of technology

It realizes the formation of a dense and uniform molybdenum disulfide film layer on the surface of threaded fasteners, solves the problems of uneven coating thickness and poor locking performance, and meets the efficient lubrication and wear resistance of fasteners.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570341A_ABST
    Figure CN119570341A_ABST
Patent Text Reader

Abstract

The invention relates to molybdenum disulfide slurry for fastener electrophoretic coating, a preparation method of the molybdenum disulfide slurry and a fastener electrophoretic coating method, and belongs to the technical field of metal fastener lubricating coatings. The molybdenum disulfide slurry is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoresis resin and water. The mass ratio of the molybdenum disulfide to the epoxy acrylic acid cathode electrophoresis resin to the water is (4-5): (16-25): (75-80); the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4-5%; the particle size of the molybdenum disulfide is 0.5-2 microns; the conductivity of the molybdenum disulfide slurry does not exceed 800 [mu] S / cm; the pH value of the molybdenum disulfide slurry is 6-6.8. The molybdenum disulfide slurry is a metal grey blue stable water-based uniform emulsion in appearance, has no floating objects, is not layered, has no effective component sedimentation, and is suitable for electrophoretic coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molybdenum disulfide slurry for electrophoretic coating of fasteners and a preparation method thereof and a fastener electrophoretic coating method, belonging to the technical field of lubricating coatings for metal fasteners. Background Art

[0002] Dry film lubrication is to form a solid lubricating coating on the surface of the friction pair by physical deposition, chemical reaction or evaporative deposition, so that friction occurs between the lubricating coatings, thereby achieving friction reduction and wear resistance. Molybdenum disulfide dry film lubricant coating is a surface treatment method for aerospace fasteners. It mainly plays the role of reducing the friction of thread pairs, preventing contact corrosion, and improving assembly efficiency and quality.

[0003] Conventional coating methods mainly include brushing, dipping and spraying, among which brushing is mainly used for large structural parts or components, and the requirements for thickness and appearance quality are not very high. At present, dipping is often used for products with internal threads or deep hole structures to obtain a relatively ideal molybdenum disulfide coating thickness and adhesion at the internal threads or deep hole structures. For example, the Chinese invention patent application with a publication date of June 16, 2010 and a publication number of CN101733237A for a coating method and equipment of a dry film lubricant, the Chinese invention patent application with a publication date of February 2, 2024 and a publication number of CN117483180A for a fastener aluminum coating, a molybdenum disulfide dry film lubricant coating coating device and method, and the Chinese invention patent application with a publication date of July 5, 2024 and a publication number of CN118287349A for a fastener surface coating coating method all start from the dipping process and equipment to improve the coating quality and avoid the problems of flow marks, nodules and uneven film thickness on the coating surface. Spraying is also used for products without internal threads or deep hole structures. The coating adhesion obtained by this method is relatively ideal. However, for small-sized threaded fasteners, due to the limitation of the spraying trajectory, the uniformity of the coating thickness at the thread is difficult to ensure.

[0004] Electrophoretic coating is a coating method that uses an external electric field to make particles such as pigments and resins suspended in the electrophoretic liquid migrate in a directional manner and deposit on the substrate surface of one of the electrodes. An important feature of this coating method is that the coating film thickness is uniform, and all parts of the workpiece, such as the inner layer, depressions, welds, etc., can obtain a uniform and smooth paint film, which can solve the coating problem of other coating methods for complex-shaped workpieces. So far, there have been reports on the electrophoretic coating of molybdenum disulfide, such as "Research on electrophoretic deposition of MoS2 solid lubricating film" (Vacuum and Cryogenics, 1999, 5(2):88-93), "Molybdenum disulfide electrophoretic coating process" (Agricultural Machinery, 1974, (3):15-17), "Molybdenum disulfide electrophoretic coating" (Forging Equipment and Manufacturing Technology, 1970, (3):45-47), "Molecular electrophoretic coating of nano-molybdenum disulfide lubricating coating process design" (Shanghai Chemical Industry, 2020, 45(6):27-29). However, most of the related studies have explored the feasibility of electrophoretic coating of molybdenum disulfide from a mechanistic perspective.

[0005] The Chinese invention patent application with a publication date of January 4, 2019 and publication number CN109137046A discloses a preparation process of a molecular electrophoretic nano-molybdenum disulfide coating, which comprises the following steps: (1) mixing nano-molybdenum disulfide powder, anionic or cationic aqueous resin and functional additives uniformly to prepare an electrophoretic plating solution for standby use; (2) subjecting the workpiece to degreasing, dust removal, sandblasting, cleaning and drying until it is free of water; (3) placing the workpiece in the electrophoretic plating solution, loading a charge field in the electrophoretic plating solution, so that the anode (or cathode) ions in the electrophoretic plating solution carry nano-molybdenum disulfide molecules, bonding resin molecules and auxiliary agent ions for directional movement, and depositing a nano-molybdenum disulfide film layer on the surface of the workpiece; (4) taking the workpiece out of the electrophoretic plating solution, cleaning, curing and cooling, the workpiece is obtained. The Chinese invention patent application with a publication date of January 26, 2024 and a publication number of CN117448917A discloses a method for electrophoresis of molybdenum disulfide on a molybdenum spray coating on a piston ring, specifically disclosing the following steps: cleaning, oiling, and polishing the piston ring; using the piston ring as an anode and stainless steel as a cathode, electrophoresis is performed by passing direct current under the condition of adding an electrophoresis tank liquid containing molybdenum disulfide, wherein the applied voltage is 1.5-3.0V and the current is 160-320mA; rinsing the electrophoretic piston ring to remove the electrophoretic paint attached to the molybdenum spray coating; pre-curing and curing the cleaned piston ring; removing the oxide layer and rinsing to obtain a piston ring with electrophoretic molybdenum disulfide on the molybdenum spray coating. Although both of these Chinese invention patent applications disclose the use of electrophoresis to prepare a molybdenum dioxide coating on a workpiece, neither of them deeply considers the uniformity of the electrophoretic molybdenum disulfide coating on small-sized threaded fasteners. Summary of the invention

[0006] The first object of the present invention is to provide a molybdenum disulfide slurry for electrophoretic coating of fasteners, and to provide a molybdenum disulfide slurry suitable for electrophoretic coating of fasteners and having good stability and lubricity.

[0007] The second object of the present invention is to provide a method for preparing molybdenum disulfide slurry for electrophoretic coating of fasteners, and to provide a method for preparing molybdenum disulfide slurry with good stability and lubricity and suitable for electrophoretic coating of fasteners.

[0008] The third object of the present invention is to provide a fastener electrophoretic coating method, providing an electrophoretic coating method that can form a dense and uniform molybdenum disulfide film layer on the surface of a threaded fastener.

[0009] In order to achieve the above object, the technical solution of a molybdenum disulfide slurry for electrophoretic coating of fasteners in the present invention is: A molybdenum disulfide slurry for electrophoretic coating of fasteners, the molybdenum disulfide slurry mainly consisting of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of the molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is (4-5): (16-25): (75-80); the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4-5%; the particle size of the molybdenum disulfide is 0.5-2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6-6.8.

[0010] The beneficial effect of the above technical solution is that the molybdenum disulfide slurry for electrophoretic coating of fasteners of the present invention is an improved invention. The appearance of the molybdenum disulfide slurry for electrophoretic coating of fasteners provided by the present invention is a metallic gray-blue stable aqueous uniform emulsion, without floating matter, without stratification, and without sedimentation of effective ingredients. It has high stability itself and can form a dense and uniform molybdenum disulfide film layer on the surface of threaded fasteners. The present invention ensures that the molybdenum disulfide slurry has a very high stability by strictly controlling the particle size of molybdenum disulfide, so that it will not have obvious sedimentation during storage and electrophoretic coating, while avoiding the decrease in lubrication properties due to too small molybdenum disulfide particles.

[0011] Furthermore, the present invention strictly controls the conductivity of the molybdenum disulfide slurry, thereby effectively avoiding emulsion demulsification due to excessively high conductivity during electrophoretic coating, thereby reducing the stability of the slurry.

[0012] As a further improvement, the molybdenum disulfide slurry includes a pH regulator.

[0013] As a further improvement, the pH adjuster is one of formic acid, acetic acid and lactic acid.

[0014] Specifically, the epoxy acrylic cathode electrophoretic resin must be positively charged, and organic acid is needed to neutralize the amine groups on the resin into quaternary ammonium salts. Moreover, compared with the inorganic acid system, the use of organic acid to adjust the pH of the molybdenum disulfide slurry can, on the one hand, avoid the influence of metal ions introduced by inorganic acid on the stability of the molybdenum disulfide slurry; on the other hand, the organic acid has better buffering properties and can better maintain the pH of the molybdenum disulfide slurry.

[0015] As a further improvement, the model of the epoxy acrylic cathode electrophoretic resin is CS9800A; the total solid content of the molybdenum disulfide slurry is 8-12%.

[0016] In order to achieve the above object, the technical scheme of a method for preparing molybdenum disulfide slurry for electrophoretic coating of fasteners in the present invention is: A method for preparing molybdenum disulfide slurry for electrophoretic coating of fasteners comprises the following steps: dispersing epoxy acrylic acid cathode electrophoretic resin and molybdenum disulfide in water, adjusting pH and then grinding and filtering.

[0017] The beneficial effect of the above technical solution is that the preparation method of the present invention is easy to operate and does not require complicated instruments and equipment, and can prepare molybdenum disulfide slurry for electrophoretic coating of fasteners with good stability, which is conducive to practical industrial production.

[0018] In order to achieve the above-mentioned object, a technical solution of a fastener electrophoretic coating method in the present invention is: A method for electrophoretic coating of fasteners, comprising: using a pretreated fastener as a cathode, electrophoretically coating the fastener in the molybdenum disulfide slurry for electrophoretic coating of fasteners as claimed in any one of claims 1 to 4, and curing the fastener; the voltage applied during the electrophoretic coating is 45 to 60 V, and the power-on time is 60 to 150 s.

[0019] The beneficial effect of the above technical solution is that: the present invention uses the provided molybdenum disulfide slurry for electrophoretic coating of fasteners as the electrophoretic liquid, and develops a method for electrophoretic coating of fasteners by adjusting the applied voltage and electrophoresis time of electrophoresis. The electrophoretic coating method of the present invention can control the thickness of the molybdenum disulfide coating to 5 to 12 μm, and form a dense and uniform molybdenum disulfide film layer on the surface of the workpiece, which effectively solves the problem that it is difficult to ensure the uniformity of the molybdenum disulfide coating on small-sized threaded fasteners. Moreover, it can also meet the locking performance of threaded fasteners.

[0020] As a further improvement, the temperature of the electrophoretic coating is 20-40°C.

[0021] As a further improvement, the distance between the cathode and the anode during the electrophoretic coating is 200-400 mm.

[0022] As a further improvement, the curing treatment is performed at 165-170° C. for 20-30 min.

[0023] As a further improvement, the thickness of the molybdenum disulfide coating after electrophoretic coating is 5-12 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a cross-sectional view of a molybdenum disulfide coating prepared in Example 5 of the present invention; Figure 2 This is a cross-sectional view of the molybdenum disulfide coating prepared in Comparative Example 9 of the present invention. DETAILED DESCRIPTION

[0025] In the prior art, the production of molybdenum disulfide lubricating coating on the surface of workpieces is often done by brushing, dipping and spraying. However, brushing is mainly used in scenarios where the requirements for thickness and appearance quality are not very high; while the coating adhesion of spraying is relatively ideal, but for small-sized threaded fasteners, due to the limitation of the spraying trajectory, the thickness uniformity of the coating at the thread is difficult to ensure. Based on this, the present invention provides a molybdenum disulfide slurry for electrophoretic coating of fasteners, the molybdenum disulfide slurry is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is (4-5): (16-25): (75-80); the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4~5%; the particle size of the molybdenum disulfide is 0.5~2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6~6.8.

[0026] The present invention ensures that the molybdenum disulfide slurry has a very high stability by strictly controlling the particle size of molybdenum disulfide, so that no obvious sedimentation occurs during storage and electrophoretic coating, while avoiding the reduction in lubrication properties due to too small molybdenum disulfide particles. Furthermore, the present invention effectively avoids the reduction in slurry stability due to electrolytic side reactions during electrophoretic coating by strictly controlling the conductivity of the molybdenum disulfide slurry. The molybdenum disulfide slurry for electrophoretic coating of fasteners provided by the present invention has an appearance of a metallic gray-blue stable aqueous uniform emulsion, without floating matter, stratification, and no sedimentation of effective ingredients. It has high stability itself and can form a dense and uniform molybdenum disulfide film layer on the surface of threaded fasteners.

[0027] The present invention also provides a method for electrophoretic coating of fasteners, wherein the pretreated fasteners are used as cathodes, electrophoretically coated in the molybdenum disulfide slurry for electrophoretic coating of fasteners, and cured; the voltage applied during the electrophoretic coating is 45-60 V, and the power-on time is 60-150 s.

[0028] The electrophoretic coating method of the present invention can control the thickness of the molybdenum disulfide coating to 5-12 μm, forming a dense and uniform molybdenum disulfide film layer on the surface of the workpiece, effectively solving the problem of difficulty in ensuring uniformity of molybdenum disulfide coating on small-sized threaded fasteners. Moreover, it can also meet the locking performance of threaded fasteners.

[0029] The present invention is further described below in conjunction with specific implementation methods, but the protection scope of the present invention is not limited thereto; unless otherwise specified, various reagents, instruments, etc. used in the examples are commercially available products.

[0030] The molybdenum disulfide powders used in the following embodiments of the present invention are all provided by Myrel Corporation, and the particle size specifications are 100 nm, 0.5-2 μm, and 12-16 μm, respectively; the epoxy acrylic cathode electrophoretic resin CS9800A is provided by Badful Corporation, and its solid content is 30%.

[0031] In the following examples, the conductivity of water is measured using a conductivity meter, and the specific process is a routine operation in the art.

[0032] 1. Specific embodiments of a molybdenum disulfide slurry for electrophoretic coating of fasteners and a preparation method thereof according to the present invention: Example 1 The molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of the molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is 4:16:80; the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4~5%; the particle size of the molybdenum disulfide is 0.5~2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6~6.8; the total solid content of the molybdenum disulfide slurry is 8.8%.

[0033] The preparation method of the molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is as follows: (1) Wash 400 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 1600 g of epoxy acrylic acid cathode electrophoretic resin in 8000 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with formic acid as a pH adjuster; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry A for electrophoretic coating of fasteners.

[0034] Example 2 The molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is 4:20:76; the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4~5%; the particle size of the molybdenum disulfide is 0.5~2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6~6.8; the total solid content of the molybdenum disulfide slurry is 10%.

[0035] The preparation method of the molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is as follows: (1) Wash 400 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 2000 g of epoxy acrylic acid cathode electrophoretic resin in 7600 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with acetic acid as a pH adjuster; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry B for electrophoretic coating of fasteners.

[0036] Example 3 The molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is 5:20:75; the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4~5%; the particle size of the molybdenum disulfide is 0.5~2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6~6.8; the total solid content of the molybdenum disulfide slurry is 11%.

[0037] The preparation method of the molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is as follows: (1) Wash 500 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 2000g of epoxy acrylic acid cathode electrophoretic resin in 7500g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with a pH regulator lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry C for electrophoretic coating of fasteners.

[0038] Example 4 The molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is 5:25:75; the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4~5%; the particle size of the molybdenum disulfide is 0.5~2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6~6.8; the total solid content of the molybdenum disulfide slurry is 11.9%.

[0039] The preparation method of the molybdenum disulfide slurry for electrophoretic coating of fasteners in this embodiment is as follows: (1) Wash 500 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 2500 g of epoxy acrylic acid cathode electrophoretic resin in 7500 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with acetic acid as a pH adjuster; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry D for electrophoretic coating of fasteners.

[0040] 2. A specific embodiment of a fastener electrophoretic coating method of the present invention: Example 5 In this embodiment, the molybdenum disulfide slurry A for electrophoretic coating of fasteners prepared in Example 1 is used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) Thirty M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 200 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry A for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 45 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 20°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0041] Example 6 In this embodiment, the molybdenum disulfide slurry B for electrophoretic coating of fasteners prepared in Example 2 is used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) 20 M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 250 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry B for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 50 V, the peak current does not exceed 1 A, and the power-on time is 150 s; the electrophoretic coating temperature is 30°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0042] Example 7 In this embodiment, the molybdenum disulfide slurry C for electrophoretic coating of fasteners prepared in Example 3 is used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) Ten M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 300 mm. (3) Electrophoretic coating is performed in molybdenum disulfide slurry C for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 55 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 25°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 170°C for 20 minutes.

[0043] Example 8 In this embodiment, the molybdenum disulfide slurry D for electrophoretic coating of fasteners prepared in Example 4 is used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: (1) After sandblasting, clean the M5 fasteners made of GH4169 with hot water and blow dry; (2) 20 M5 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 400 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry D for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 60 V, the peak current does not exceed 1 A, and the power-on time is 90 s; the electrophoretic coating temperature is 35°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 170°C for 20 minutes.

[0044] Example 9 In this embodiment, the molybdenum disulfide slurry A for electrophoretic coating of fasteners prepared in Example 1 is used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: (1) After sandblasting, clean the M5 fasteners made of GH4169 with hot water and blow dry; (2) Thirty M5 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 350 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry A for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 55 V, the peak current does not exceed 1 A, and the power-on time is 60 s; the electrophoretic coating temperature is 40°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0045] Example 10 In this embodiment, the molybdenum disulfide slurry B for electrophoretic coating of fasteners prepared in Example 2 is used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: (1) After sandblasting, clean the M5 fasteners made of GH4169 with hot water and blow dry; (2) 20 M5 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 250 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry B for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 45 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 40°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0046] 3. Comparative Proportion Comparative Example 1 In this comparative example, the molybdenum disulfide slurry A for electrophoretic coating of fasteners prepared in Example 1 was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) Thirty M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 500 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry A for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 45 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 20°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0047] Comparative Example 2 In this comparative example, the molybdenum disulfide slurry A for electrophoretic coating of fasteners prepared in Example 1 was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) Thirty M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 150 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry A for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 45 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 20°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0048] Comparative Example 3 In this comparative example, the molybdenum disulfide slurry B for electrophoretic coating of fasteners prepared in Example 2 was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) 20 M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 250 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry B for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 70 V, the peak current does not exceed 1 A, and the power-on time is 150 s; the electrophoretic coating temperature is 30°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0049] Comparative Example 4 In this comparative example, the molybdenum disulfide slurry B for electrophoretic coating of fasteners prepared in Example 2 was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) 20 M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 250 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry B for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 40 V, the peak current does not exceed 1 A, and the power-on time is 150 s; the electrophoretic coating temperature is 30°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 165°C for 30 minutes.

[0050] Comparative Example 5 In this comparative example, the molybdenum disulfide slurry C for electrophoretic coating of fasteners prepared in Example 3 was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: (1) The M6 ​​fasteners made of SUS316L material are pre-treated by cleaning, pickling and passivation according to the HB / Z 83 process requirements; (2) Ten M6 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 300 mm. (3) Electrophoretic coating is performed in molybdenum disulfide slurry C for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 55 V, the peak current does not exceed 1 A, and the power-on time is 120 s; the electrophoretic coating temperature is 45°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 170°C for 20 minutes.

[0051] Comparative Example 6 In this comparative example, the molybdenum disulfide slurry D for electrophoretic coating of fasteners prepared in Example 4 was used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: (1) After sandblasting, clean the M5 fasteners made of GH4169 with hot water and blow dry; (2) 20 M5 fasteners are mounted with conductive wire and used as cathodes. The counter electrode is an anode system consisting of stainless steel and a semipermeable membrane. The distance between the electrodes is kept at about 400 mm. (3) Electrophoretic coating is performed on molybdenum disulfide slurry D for electrophoretic coating of fasteners by a constant voltage method with initial current control; wherein the applied voltage is 60 V, the peak current does not exceed 1 A, and the power-on time is 90 s; the electrophoretic coating temperature is 15°C; (4) After electrophoresis, pre-curing and curing are performed. The pre-curing conditions are 100°C for 20 minutes, and the curing conditions are 170°C for 20 minutes.

[0052] Comparative Example 7 In this comparative example, molybdenum disulfide slurry E was prepared, and the slurry was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: 1. Preparation of MoS2 Slurry E (1) Wash 500 g of micronized molybdenum disulfide powder (12-16 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 1600 g of epoxy acrylic acid cathode electrophoretic resin in 8000 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with a pH regulator lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 10 μm; (5) The slurry prepared in step (4) is filtered through a 1250-mesh filter, and the filtrate is the molybdenum disulfide slurry E for electrophoretic coating of fasteners.

[0053] 2. Electrophoretic coating The specific electrophoretic coating process is as described in Example 7.

[0054] Comparative Example 8 In this comparative example, molybdenum disulfide slurry F was prepared, and the slurry was used to electrophoretically coat M6 fasteners made of SUS316L material. The specific implementation operation is as follows: 1. Preparation of MoS2 Slurry F (1) Wash 400 g of micronized molybdenum disulfide powder (100 nm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 2000 g of epoxy acrylic acid cathode electrophoretic resin in 7600 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with a pH regulator lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250 mesh filter, and the filtrate is the molybdenum disulfide slurry F for electrophoretic coating of fasteners.

[0055] 2. Electrophoretic coating The specific electrophoretic coating process is as described in Example 5.

[0056] Comparative Example 9 In this comparative example, molybdenum disulfide slurry G was prepared, and the slurry was used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: 1. Preparation of MoS2 Slurry G (1) Wash 500 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 4000 g of epoxy acrylic acid cathode electrophoretic resin in 5500 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with a pH regulator lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry G for electrophoretic coating of fasteners.

[0057] 2. Electrophoretic coating The specific electrophoretic coating process is as described in Example 8.

[0058] Comparative Example 10 In this comparative example, molybdenum disulfide slurry H was prepared, and the slurry was used to electrophoretically coat M5 fasteners made of GH4169 material. The specific implementation operation is as follows: 1. Preparation of MoS2 Slurry H (1) Disperse 1600 g of epoxy acrylic cathode electrophoretic resin in 8000 g of pure water and stir evenly; (2) 400 g of micronized molybdenum disulfide powder (0.5-2 μm) is uniformly dispersed in the solution of step (2), and the pH is adjusted to 6-6.8 with a pH regulator, lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250-mesh filter, and the filtrate is the molybdenum disulfide slurry H for electrophoretic coating of fasteners.

[0059] 2. Electrophoretic coating The specific electrophoretic coating process is as described in Example 9.

[0060] Comparative Example 11 In this comparative example, molybdenum disulfide slurry I was prepared, and the slurry was used to electrophoretically coat M6 fasteners made of GH4169 material. The specific implementation operation is as follows: 1. Preparation of Molybdenum Disulfide Slurry I (1) Wash 500 g of micronized molybdenum disulfide powder (0.5-2 μm) with 6 L of pure water until the conductivity of the washed water does not exceed 500 μS / cm at 25°C; (2) Disperse 1000 g of epoxy acrylic acid cathode electrophoretic resin in 8500 g of pure water and stir evenly; (3) The washed micronized molybdenum disulfide powder is uniformly dispersed in the solution of step (2) according to the formula amount, and the pH is adjusted to 6-6.8 with a pH regulator lactic acid; (4) grinding the slurry of step (3) using a pigment grinding device so that the fineness of molybdenum disulfide does not exceed 2 μm; (5) The slurry prepared in step (4) is filtered through a 6250 mesh filter, and the filtrate is the molybdenum disulfide slurry I for electrophoretic coating of fasteners.

[0061] 2. Electrophoretic coating The specific electrophoretic coating process is as described in Example 10.

[0062] IV. Experimental Examples Experimental Example 1 Slurry Property Detection This experimental example tests the properties of molybdenum disulfide slurries A to D for electrophoretic coating of fasteners prepared in Examples 1 to 4 and molybdenum disulfide slurries E to I prepared in Comparative Examples 7 to 11. The specific operation is as follows: The properties of the molybdenum disulfide slurries A-D for electrophoretic coating of fasteners prepared in Examples 1-4 and the molybdenum disulfide slurries E-I prepared in Comparative Examples 7-11 are shown in Table 1.

[0063] Table 1 Properties of MoS2 slurry * After standing for 48 hours, observe and if there is sedimentation of molybdenum disulfide slurry or flocculation of epoxy acrylic resin, it is considered unstable.

[0064] It can be seen from Table 1 that molybdenum disulfide slurries A, B, C, D, F, and G are stable. Molybdenum disulfide slurry E is unstable because the molybdenum disulfide particles are too large and the molybdenum disulfide particles are obviously settled; molybdenum disulfide slurry H is unstable because the molybdenum disulfide is not washed with water and the conductivity is too high, resulting in emulsion demulsification; molybdenum disulfide slurry I is unstable because the amount of epoxy acrylic resin is too little and the molybdenum disulfide particles are obviously settled.

[0065] Experimental Example 2 Fastener Coating Performance This experimental example evaluates the performance of molybdenum disulfide coatings on fasteners after electrophoretic coating in Examples 5 to 10 and Comparative Examples 1 to 11. The specific implementation operations are as follows: The performance of the molybdenum disulfide coating on the fasteners after electrophoretic coating in Examples 5 to 10 and Comparative Examples 1 to 11 was evaluated, and the specific results are shown in Table 2.

[0066] Table 2 Properties of electrophoretic MoS2 coating *1 The fasteners were cut open by wire cutting and observed using a scanning electron microscope. Two fasteners were observed at 10 locations each. All the thicknesses were within 5 to 12 μm and were considered acceptable. *2 Three fasteners were tested using the national standard GB / T 9286 tape method. If the coating did not fall off, it was considered qualified. *3 Tightening torque: The maximum tightening torque is ≤3.4 N•m; the minimum tightening torque is 0.39≥N•m, which is considered qualified.

[0067] The following conclusions can be drawn from Table 2: (1) From the test results of Example 5, Comparative Example 1 and Comparative Example 2, it can be seen that the electrode distance of Comparative Example 1 is 500, which is higher than the reasonable range of 200-400 mm, and the coating thickness of the electrophoretic coating is thin, not in the range of 5-12 μm. The electrode distance of Comparative Example 2 is 150, which is lower than the reasonable range of 200-400 mm, and the coating thickness of the electrophoretic coating is thick, not in the range of 5-12 μm. From the test results of Example 6, Comparative Example 3 and Comparative Example 4, it can be seen that the electrophoretic voltage of Comparative Example 3 is 70 V, which is higher than the reasonable range of 45-60 V, and the coating thickness of the electrophoretic coating is thick, and the coating thickness is not in the range of 5-12 μm. The electrophoretic voltage of Comparative Example 4 is 40 V, which is lower than the reasonable range of 45-60 V, and the coating thickness of the electrophoretic coating is thick, and the coating thickness is not in the range of 5-12 μm range; from Example 7, Example 8, Comparative Example 5, and Comparative Example 6, the test results show that the electrophoretic coating temperature of Comparative Example 5 is 45°C, which is higher than the reasonable range of 20-40°C, and the coating thickness of the electrophoretic coating is thicker, and the coating thickness is not in the range of 5-12 μm; the electrophoretic coating temperature of Comparative Example 6 is 15°C, which is lower than the reasonable range of 20-40°C, and the coating thickness of the electrophoretic coating is thinner, and the coating thickness is not in the range of 5-12 μm.

[0068] (2) In Comparative Example 7, slurry E used molybdenum disulfide with a particle size of 12-16 μm. The particles were too large, and the molybdenum disulfide was obviously precipitated, and a complete coating could not be formed.

[0069] (3) In Comparative Example 8, slurry F uses 100 nm molybdenum disulfide, which has too small particles. Although the film thickness and adhesion meet the composite requirements, the locking performance does not meet the requirements.

[0070] (4) In Comparative Example 9, slurry G uses molybdenum disulfide with a particle size of 0.5 to 2 μm, but the epoxy acrylic resin content is too high, resulting in a low content of molybdenum disulfide in the coating, which makes the maximum screw-in value too large.

[0071] (5) In Comparative Example 10, slurry H was used. Due to its high conductivity, the slurry was unstable and could not form a complete coating. In Comparative Example 10, slurry I was used. Due to its low content of epoxy acrylic resin, the slurry was unstable and could not form a complete coating.

[0072] (6) Figure 2 This is a cross-sectional view of the coating of Comparative Example 9. It can be seen from the figure that the molybdenum disulfide particles in the prepared coating are unevenly dispersed.

[0073] (7) Figure 1 This is a cross-sectional view of the coating prepared in Example 5. It can be seen from the figure that the molybdenum disulfide particles are evenly dispersed in the prepared coating.

[0074] (8) Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or part or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A molybdenum disulfide slurry for electrophoretic coating of fasteners, characterized in that: The molybdenum disulfide slurry is mainly composed of molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water; the mass ratio of the molybdenum disulfide, epoxy acrylic acid cathode electrophoretic resin and water is (4-5): (16-25): (75-80); the mass fraction of molybdenum disulfide in the molybdenum disulfide slurry is 4-5%; the particle size of the molybdenum disulfide is 0.5-2 μm; the conductivity of the molybdenum disulfide slurry does not exceed 800 μS / cm; the pH of the molybdenum disulfide slurry is 6-6.

8.

2. The molybdenum disulfide slurry for electrophoretic coating of fasteners according to claim 1, characterized in that: The molybdenum disulfide slurry includes a pH adjuster.

3. The molybdenum disulfide slurry for electrophoretic coating of fasteners according to claim 2, characterized in that: The pH adjuster is one of formic acid, acetic acid and lactic acid.

4. The molybdenum disulfide slurry for electrophoretic coating of fasteners according to any one of claims 1 to 3, characterized in that: The model of the epoxy acrylic acid cathode electrophoretic resin is CS9800A; the total solid content of the molybdenum disulfide slurry is 8-12%.

5. A method for preparing the molybdenum disulfide slurry for electrophoretic coating of fasteners according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: dispersing epoxy acrylic acid cathode electrophoretic resin and molybdenum disulfide in water, adjusting pH value and then grinding and filtering.

6. A method for electrophoretic coating of fasteners, characterized in that: The method comprises the following steps: using the pretreated fastener as a cathode, electrophoretically coating the fastener in the molybdenum disulfide slurry for electrophoretic coating of the fastener according to any one of claims 1 to 4, and curing; the voltage applied during the electrophoretic coating is 45 to 60 V, and the power-on time is 60 to 150 s.

7. The fastener electrophoretic coating method according to claim 6, characterized in that: The temperature of the electrophoretic coating is 20-40°C.

8. The fastener electrophoretic coating method according to claim 6, characterized in that: During the electrophoretic coating, the distance between the cathode and the anode is 200-400 mm.

9. The fastener electrophoretic coating method according to any one of claims 6 to 8, characterized in that: The curing treatment is performed at 165-170° C. for 20-30 min.

10. The fastener electrophoretic coating method according to claim 9, characterized in that: The thickness of the molybdenum disulfide coating after electrophoretic coating is 5-12 μm.

Citation Information

Patent Citations

  • Method and equipment for coating dry-film lubricant

    CN101733237A

  • Preparation process of molecular swimming plating nano-molybdenum disulfide coatings

    CN109137046A

  • Fastener aluminum coating and molybdenum disulfide dry film lubricant coating coating device and method

    CN117483180A

  • Fastener surface coating coating method

    CN118287349A

  • Cathode two-component electrophoretic paint coating process with relatively good bath solution stability

    CN115044905A